Law and poverty in Australia : 40 years after the Poverty Commission - Durbach, Andrea; Edgeworth, Brendan; Sentas, Victoria (Annandale, NSW : The Federation Press, 2017)
The publication of the Poverty Commission's Law and Poverty in Australia Report (the Sackville Report) in 1975 was a landmark event in the history of Australian law reform, however since that time Australia has become a more unequal society. This book provides an inventory of progress made over the past four decades with regard to the many proposals contained in the original Law and Poverty Report. The overall conclusion is that the scorecard is uneven. Substantial implementation of the reforms has occurred in many areas, such as consumer and tenancy law. Despite initial progress in other areas, such as tax law, legal aid and social security, there has been deterioration. It also highlights some important aspects of poverty and law not contained in the original Report: the intersection of the experiences of LGBTI people, poverty and law; the international dimension of law and poverty in light of globalisation; and the critical importance of tax rules in relation to poverty. The book concludes by identifying critical areas for reform to address the legal problems that poor people confront.
Includes bibliographical references and index.
Keywords: Australia -- Commission of Inquiry into Poverty; Law -- Social aspects -- Australia; Poverty -- Social aspects -- Australia; Social legislation -- Australia -- Evaluation; Social structure -- Australia